RURAL HOUSEHOLD FOOD SECURITY IN KUDUS CENTRAL JAVA - Hannavi, Iin Endya; Ferichani, Minar; Antriyandarti, Ernoiz; Ani, Susi Wuri (Fakultas Pertanian Universitas Muhammadiyah Jember, 2018)
Evidence of previous studies indicated that food security is a common problem in most areas of the world. This study aims to determine the proportion of food consumption expenditure on total of rural household expenditure, rural household food security conditions, and factors influencing food security of rural households in Kudus District. To estimate the factors influencing food security, a series of models is created. Pooled least square regression is used to estimate the factors. Â This study indicate that the average proportion of food expenditure on total household expenditure is 56.4%. Food vulnerability is the highest category of food security conditions of rural household in Kudus District which reached an average level of energy consumption is 113,42% with food expenditure proportion equal to 73,15%. Based on analysis there are eight factors from ten factors used by researchers have influenced household food security in terms of energy consumption, while there are seven factors that affecting food security seen from household protein consumption. The analysis of the factors influencing food security in rural household in Kudus District shows that side jobs have two contradictory impacts reviewed from energy and protein consumption. This research also finds out that eggs real price does not have any influence toward rural household food security in Kudus District.